On the General Tendencies in Russian Classical Literature Translations to Lithuanian - Beržaitė, Dagnė (Literatūra, 2017)
This article deals with the general tendencies in Lithuanian translations of Russian classical literature. One of the main peculiarities can be described as a specific interest in lyrical poetry, while the readers of Russian novels can usually find the only Lithuanian translation of one or another book, completed more than 50 years ago. The author of the article once again examines the history of Lithuanian translations of F. Dostoevsky’s works and comes to the conclusion that the absence of high quality translations as well as the late translations of some important novels, as well as the policy of publishing the writer’s books, could be responsible for the specific reception of Dostoevsky in Lithuania. The analysis of some of Dostoevsky’s books published in Lithuanian shows that the translators of our day could devote more attention to the matters of an individual author’s style. ОБ ОБЩИХ ТЕНДЕНЦИЯХ ПЕРЕВОДА РУССКОЙ КЛАССИЧЕСКОЙ ЛИТЕРАТУРЫ НА ЛИТОВСКИЙ ЯЗЫК В статье рассматриваются общие тенденции перевода русской классической литературы на литовский язык, среди которых выделяется явное внимание к поэзии, тогда как в прозе читатели вынуждены довольствоваться наличием в основном одного-единственного перевода, и то осуществленного в лучшем случае более полувека назад. Автор статьи, еще раз просмотрев историю литовских переводов твочества Ф. М. Достоевского, приходит к заключению, что наличие не самых качественных переводов, отсутствие на литовском языке вплоть до ХХI в. главных текстов писателя, а также политика их издания не могли не способствовать формированию специфического восприятия писателя в Литве в целом. Осуществленный в статье анализ некоторых до сих пор не изученных литовских переводов произведений Достоевского позволяет сделать вывод, что современные переводчики в первую очередь должны были бы обратить внимание на передачу индивидульного стиля писателя.